Seni Tari Kreasi sebagai Sarana Pengembangan Kreativitas Anak Usia Dini - Al Mei Mutmainah, Amirah; Mulyani, Novi (Jurnal Pendidikan Agama Islam, 2025)
In early childhood, children's creativity needs to be stimulated through activities such as creative dance, especially amidst the challenges of globalization and the widespread use of gadgets. This study aims to examine and describe the implementation of creative dance in an effort to develop creativity in early childhood. This study uses a descriptive qualitative field research method. The results of the study indicate that creative dance activities are very effective in stimulating children's creativity through movement expression, imagination, and creative thinking. In addition, it helps support children's motoric, social, and emotional development. This activity also results in school achievements in dance competitions, although children's interests and participation vary.